ACCOMPLISHMENT OF INQUIRY SKILLS IN INQUIRY BASED WORKSHEET ON ECOSYSTEM MATTER FOR SENIOR HIGH SCOOL STUDENT CLASS X - ANIS NUR SETIYANINGSIH (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Ecosystem matter worksheet on schools, one of them is SMAN 1 Sumberrejo, Bojonegoro, have not applied inquiry activity, only contain summary and questions that only encompass explaining skills. From that, this research have purpose to detect accomplishment of inquirybased worksheet on ecosystem matter for teach skill student in critical brain. Accomplishment inquiry skill measured from obcervation 18 studens class X of SMAN 1 Sumberrejo, Bojonegoro when their aolication of LKS, and then score must analyed as discriptif. Accomplishment result of inquiry skill as 92,5%. Keywords: student worksheet, inquiry, ecosystem